THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT IN THE RELATIONSHIP BETWEEN TRAINING EFFECTIVENESS AND POLICE PERFORMANCE - Novi Indah Earlyanti; Muhammad Afifi Rahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This literature review article examines the mediating role of organizational commitment in the relationship between training effectiveness and police performance. In contemporary law enforcement environments, training is no longer perceived solely as a technical capacity-building mechanism, but as a strategic organizational process that shapes attitudes, values, and behavioral outcomes. Drawing on empirical studies published within the last decade, this review synthesizes evidence demonstrating that training effectiveness significantly influences police performance, both directly and indirectly through organizational commitment. Organizational commitment functions as a psychological and attitudinal bridge that transforms acquired competencies into consistent and sustainable performance behaviors. Using a systematic literature review approach, this study analyzes twenty-five peer-reviewed journal articles to identify recurring patterns, theoretical explanations, and contextual factors shaping this relationship. The findings reveal that training programs perceived as relevant, fair, and development-oriented foster stronger affective and normative commitment, which in turn enhances task performance, ethical conduct, and service quality among police personnel. The review also highlights gaps in existing research, particularly the limited integration of commitment theory into police training evaluation frameworks. The article concludes by emphasizing the strategic importance of embedding commitment-oriented dimensions into police training systems to strengthen institutional effectiveness and public trust.